Trastuzumab-resistant breast cancer cells remain sensitive to the auger electron-emitting radiotherapeutic agent 111In-NLS-trastuzumab and are radiosensitized by methotrexate. - Costantini, D; Bateman, K; McLarty, K; Vallis, K; Reilly, R (2008)
UNLABELLED: Our goals in this study were to determine whether (111)In-trastuzumab coupled to peptides harboring nuclear localizing sequences (NLSs) could kill trastuzumab-resistant breast cancer cell lines through the emission of Auger electrons and whether the combination of radiosensitization with methotrexate (MTX) would augment the cytotoxicity of this radiopharmaceutical. METHODS: Trastuzumab was derivatized with sulfosuccinimidyl-4-(N-maleimidomethyl)cyclohexane-1-carboxylate for reaction with NLS peptides and then conjugated with diethylenetriaminepentaacetic acid for labeling with (111)In. HER2 expression was determined by Western blot and by radioligand binding assay using (111)In-trastuzumab in a panel of breast cancer cell lines, including SK-BR-3, MDA-MB-231 and its HER2-transfected subclone (231-H2N), and 2 trastuzumab-resistant variants (TrR1 and TrR2). Nuclear importation of (111)In-NLS-trastuzumab and (111)In-trastuzumab in breast cancer cells was measured by subcellular fractionation, and the clonogenic survival of these cells was determined after incubation with (111)In-NLS-trastuzumab, (111)In-trastuzumab, or trastuzumab (combined with or without MTX). Survival curves were analyzed according to the dose-response model, and the radiation-enhancement ratio was calculated from the survival curve parameters. RESULTS: The expression of HER2 was highest in SK-BR-3 cells (12.6 x 10(5) receptors/cell), compared with 231-H2N and TrR1 cells (6.1 x 10(5) and 5.1 x 10(5) receptors/cell, respectively), and lowest in MDA-MB-231 and TrR2 cells (0.4 x 10(5) and 0.6 x 10(5) receptors/cell, respectively). NLS peptides increased the nuclear uptake of (111)In-trastuzumab in MDA-MB-231, 231-H2N, TrR1, and TrR2 cells from 0.1%+/-0.01%, 2.5%+/-0.2%, 2.8%+/-0.7%, and 0.5%+/-0.1% to 0.5%+/-0.1%, 4.6%+/-0.1%, 5.2%+/-0.6%, and 1.5%+/-0.2%, respectively. The cytotoxicity of (111)In-NLS-trastuzumab on breast cancer cells was directly correlated with the HER2 expression densities of the cells. On a molar concentration basis, the effective concentration required to kill 50% of 231-H2N and TrR1 cells for (111)In-NLS-trastuzumab was 9- to 12-fold lower than for (111)In-trastuzumab and 16- to 77-fold lower than for trastuzumab. MDA-MB-231 and TrR2 cells were less sensitive to (111)In-NLS-trastuzumab or (111)In-trastuzumab, and both cell lines were completely insensitive to trastuzumab. The radiation-enhancement ratio induced by MTX for 231-H2N and TrR1 cells after exposure to (111)In-NLS-trastuzumab was 1.42 and 1.68, respectively. CONCLUSION: Targeted Auger electron radioimmunotherapy with (111)In-NLS-trastuzumab can overcome resistance to trastuzumab, and MTX can potently enhance the sensitivity of HER2-overexpressing breast cancer cells to the lethal Auger electrons emitted by this radiopharmaceutical.